Efeitos da correção textual-interativa em textos de alunos do 5º ano do ensino fundamental - Pedro, Fernanda Sacomori Candido (2020)
According to the National Curriculum Parameters of Portuguese Language (PCN), the teaching of writing must be guided by the concrete form in which it presents itself in different circumstances of human interaction. This assumption, anchored in the theoretical focus of the dialogical and interactional conception of language, proposed by Bakhtin's circle, comprises the text / statement as the organizing element of the discursive process, that is, language only has real meaning in the interaction, when we use it with the objective of constituting ourselves as subjects of speech. In this sense, in the textual production, it is necessary that the forwarding of the writing takes into account a real communication situation, in which it is clear to whom it is intended, for what purpose and under what circumstances it will be done. Thus, the production of texts would involve planning, writing, proofreading and rewriting. The review and rewriting of texts are stages of the textual production process, together with planning and writing, in which the text is taken up in its linguistic, textual and discursive elements, in order to make it suitable for the communicative purpose. However, as teachers of basic education, we observe in our reality a distance from this practice that considers textual production in stages. As explained in the conception of writing as work, Fiad and Mayrink-Sabinson (1991) emphasize that, in general, this teaching unit is used in a way unrelated to its social function and, therefore, considered ready and finished in the first version. For this reason, we chose, in this study, to focus on textual production as a whole, while emphasizing revision and rewriting. Our look, therefore, turned specifically to the following theme: effects of textual-interactive correction in students' texts. This option is justified by evaluating that, in our work with the written production of our students, this practice of intervention of textual-interactive correction, proposed by Ruiz (2010), was absent, and this could be a factor that would be hindering a writing more efficient, from the point of view of interaction. Based on this investigative purpose, we ask ourselves: does the revision and textual rewriting carried out from textual-interactive correction promote improvements in linguistic, textual and discursive aspects in texts of students in the 5th year of elementary school? Thus, our general objective in carrying out this work was to analyze the effects of textual-interactive correction aimed at linguistic, textual and discursive aspects, in the process of revision and rewriting of texts. The research is circumscribed in the area of Applied Linguistics, based on the assumptions of the dialogical and interactionist conception of language, according to Bakhtin (2003 and 2006) and Geraldi (1997, 2006); in the conception of writing as work, according to Fiad and Mayrink-Sabinson (1991); and in the forms of correction explained by Ruiz (2010), using action research as a methodological procedure, given that we analyze our own practice. The results obtained throughout the research process enabled us to realize: a) that it is necessary for teachers to know about this conception of writing that proposes the review and rewriting for all textual production with the objective of interaction; b) that our mediation, as teachers in these stages, is essential, since our view as readers interacting with students is what will provide their reflection on their production; c) that this work with the language carried out in the stages of revision and rewriting needs to be started in elementary school; d) that it is important to use textual production as a starting point for linguistic analysis work, aligning this moment of reflection with the language to the student's needs; e) that the form of intervention used by the teacher at the time of the review has a lot to do with the results obtained by the students in the rewriting, because depending on our interventionist technique, we promote reflection and student participation that will be more effective the more dialogical it is; f) that this interventional technique that we use in the students' texts, requires time and energy from the teacher in addition to his weekly workday, which justifies the expansion of the hour-activity for the Portuguese language teacher; g) that the textual-interactive correction provides effective student participation, as the texts have undergone changes in both linguistic, textual and discursive aspects and the students have demonstrated their responsiveness and, thus, their constitution as the authors of their subjects. speeches.